If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(v + -2) + -6v = 0 Reorder the terms: 3(-2 + v) + -6v = 0 (-2 * 3 + v * 3) + -6v = 0 (-6 + 3v) + -6v = 0 Combine like terms: 3v + -6v = -3v -6 + -3v = 0 Solving -6 + -3v = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -3v = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -3v = 0 + 6 -3v = 0 + 6 Combine like terms: 0 + 6 = 6 -3v = 6 Divide each side by '-3'. v = -2 Simplifying v = -2
| 4(4-7n)=2(8-n) | | -6x+-5x= | | (46+2x)(65+2x)=4740 | | 3r^2-24r+45=0 | | 12p^2+8p+1=0 | | 3y^3+16y+5=0 | | 4(-b+7)=-(1+7v) | | (x-8)(x+7)=56 | | 17x+-12=114+3 | | 5g^2+44g-9=0 | | 5x+2(5x+8)=8x+18 | | 6p+-3(4p+3)+4(6p+1)=43 | | 5(m-2)=-(6m-1) | | x(x-9)(x+3)=0 | | Z-6.8=7.56 | | 0=6x+x^2-31 | | 1620x-350=680x+470 | | 1/3p-p=12 | | (8x+3)(5x+8)=180 | | 3x+9(3x+1)=9x-6 | | 6(4x+3)=138 | | 5x+9i=10-3yi | | 2x+9+9x-8=8x+19 | | 15x-3(6+5x)=-18 | | x*x=16+(x+-4)(x+2) | | 8+6y=7y | | 2x+6=-6-2 | | -4(v+7)=-(1+7v) | | 14.3=-1.4-3d | | x*x=16+(x-4)*(x+4) | | P/g=10 | | 9x-5-6x-2=6x-1 |